The positive effects of positive coping on mental health in college students during the COVID-19 campus lockdown - Li, Meiqi; Chen, Lijun (Frontiers in Public Health, 2023)
Isolation has been an effective method to control the spread of COVID-19 over the past three years. However, lifestyle changes may have a negative impact on mental health. To examine the effects of positive coping on mental health in college students during the COVID-19 campus lockdown, this study conducted an online cross-sectional survey.In October 2022, following a prolonged campus lockdown of nearly three years, 313 university students from a university in Shandong Province, China, were invited to complete an online questionnaire. The questionnaire comprised a selfadministered general situation questionnaire, the Simple Coping Style Scale , and the Hospital Depression and Anxiety Scale.(1) The analysis of variance revealed a significant main effect of coping Style on depression(F(4,300)=2.446, p=0.047) during the COVID-19 campus lockdown. A post-hoc test indicated that college students who engaged in study (p=0.012) or sports(p=0.027) during their free time had significantly lower depression scores than those who used the Internet. (2) Independent sample t-tests showed significant differences in positive and negative coping styles among college students in terms of depression(t=6.891, p<0.001) and anxiety scores(t=7.745, p<0.001). ( 3) Pearson correlation analysis demonstrated a negative correlation between positive coping style and anxiety(r=-0.378, p<0.001), and between positive coping style and depression(r=-0.427, p<0.001). Positive correlations were also found between the negative coping style and anxiety(r=0.155, p=0.007), and between the negative coping style and depression(r=0.190, p<0.001).The study suggested that fostering positive coping in students can mitigate mental health issues during crises, providing a blueprint for university mental health initiatives during epidemics.